Blended Learning Approach of the Flipped Model for Partograph Short Course - Linawati Linawati (Journal of Education and Learning (EduLearn), 2016)
Crucial demand of professional and well-trained midwives, midwifery lecturers, general practitioner, and OBGYN in Indonesia could be fulfilled by providing effective learning process to them. Udayana University through its Distance Learning Centre has offered Partograph short course in order to respond the demand. The short course has implemented blended learning approach of the flipped classroom with international collaboration. The course was joint by participants from 11 countries through video conference.  The course was well designed, conducted follow Global Development Learning Network standard, and then it was evaluated.  The course yielded high impact to the participants which could be seen from the participants’ feedback. They testified that the course was marvelous, effective and informative. Finally the evaluation results showed that all components of the learning process have significant result to the overall learning quality which was shown by their correlation coefficients.